ACQUISITION OF TEXTUAL BEHAVIOR "SAFETY" "DANGER" IN MENTALLY RETARDED CHILD - Tsurumaki, Masako (Japanese Journal of Behavior Therapy, 1994)
The present study aims at helping mentally retarded child who cannot read Chinese characters regarding "safety" and "danger" to acquire the textual behavior regarding those characters, using a simultaneous auditory-visual matching-to-sample procedure. At baseline I, he could not read Chinese characters. However at baseline)", the rate of correct response was 100%. In post checks conducted two weeks after and four weeks after the training, the rate of correct responses was also 100%. Therefore the aim of the present study, being to help the subject acquire textual behavior regarding "safety" and "danger", was fulfilled. Moreover, the subject's reaction time for auditory-visual matching is shorter at baseline II than at baseline I.